Remediating Destroyed Human Bodies: Contemporaneity and Habits of Online Visual Culture - Chau, Christina (M/C Publication, 2017)
Thomas Hirschhorn’s video artwork Touching Reality has received much critical acclaim since it was first exhibited in 2012. First shown at the Palais de Tokyo in 2012, the artwork has since exhibited at the Institute of Modern Art in Brisbane (2013), and a recording of the piece installed can be currently found on Vimeo. The floor to ceiling video installation presents a woman’s hand scrolling through images on a touchscreen, which contains violent scenes of war where corpses that have been maimed, blown apart, destroyed, and mangled by war. Hirschhorn has explained that Touching Reality is a response to mainstream tabloid media presented in newspapers and magazines (1), and consequently Rex Butler has criticised the work for being “strangely out of date” (quoted in Johnston 9). However, the artwork resonates strongly with habits of online culture. Specifically, the remediation of images from the internet in this artwork presents, as I argue, a regard for contemporaneity that renders temporal and spatial providence of media texts as ambiguous. A key effect of this artwork then functions to historicise and monumentalise a particular approach to contemporaneity in digital culture today.